Míticas do envelhecimento: em busca de uma vida saudável - Monique Borba Cerqueira (Ciências Sociais Unisinos)
Speeches promoting quality of life and healthy aging proliferate in the contemporary social scene, introducing new meanings, representations and visibilities in the aging process. The aim of this work is to learn how healthy life ideas dialogue with the real world of those who are getting old. It is an ethnographic study with a social-anthropological perspective that assesses contemporary aging, based on its social remodeling process.